Effects of Thermal Annealing on the Properties of Mechanically Exfoliated Suspended and On-Substrate Few-Layer Graphene - Richard Cobley (Crystals, 2017)
Graphene’s novel electrical, optical, and mechanical properties are affected both by substrate interaction and processing steps required to fabricate contacts and devices. Annealing is used to clean graphene devices, but this can lead to doping and defect changes and strain effects. There is often disagreement about which of these effects are occurring and which result in observed changes in Raman spectra. The effects of vacuum annealing on mechanically exfoliated pristine, suspended, and attached thin and thick few-layer graphene on SiO2/Si are investigated here using scanning electron microscopy (SEM), Raman spectroscopy, and atomic force microscopy (AFM). Before annealing, Raman shows that the differences in 2D and G band positions and the appearance of a disorder-induced D band of all regions were mainly because of compressive or tensile structural deformations emerging through mechanical exfoliation instead of charge doping. Annealing at low temperature is sufficient to eliminate most of the defects. However, compressive strain is induced in the sheet by annealing at high temperature, and for thin regions increased substrate conformation leads to the apparent disappearance of the sheets. The intensity ratio of the 2D and G bands also reduces with induced compressive strain, and thus should not be used to detect doping.